2015
DOI: 10.1038/srep08649
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Significances of MUC5B and TTF-1 Expressions in Resected Non-Small Cell Lung Cancer

Abstract: To investigate the relationships between the expression of MUC5B and clinicopathological parameters, the expression of MUC5B was immunohistochemically studied. MUC5B expression was observed in 129 of 198 (65.2%) adenocarcinomas and in 4 of 49 (8.2%) squamous cell carcinomas (P < 0.00001). MUC5B expression was significantly associated with poorer differentiation (P = 0.0303), higher pathological TNM stage (p = 0.0153) and poorer prognosis of adenocarcinoma patients (P = 0.0017). Multivariable analysis with Cox … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 31 publications
3
28
1
Order By: Relevance
“…To verify this phenomenon, we also detected the expression of TTF-1 in these cancer cells, which also valuably reflected the intrinsic activity of TTF-1 promoter. Consistently, we found that the expression level of TTF-1 was also higher in lung cancer cells than that in other cancer cells, which was consistent with previous finding that TTF-1 was dominantly expressed in lung cancer cells, but not other types of cancer cells 24, 25, 26…”
Section: Resultssupporting
confidence: 92%
“…To verify this phenomenon, we also detected the expression of TTF-1 in these cancer cells, which also valuably reflected the intrinsic activity of TTF-1 promoter. Consistently, we found that the expression level of TTF-1 was also higher in lung cancer cells than that in other cancer cells, which was consistent with previous finding that TTF-1 was dominantly expressed in lung cancer cells, but not other types of cancer cells 24, 25, 26…”
Section: Resultssupporting
confidence: 92%
“…Recent studies with diagnoses based on the previous 2004 WHO classification, have shown that 64% to 86% of lung AC cases are positive for the TTF-1 clone 8G7G3/1 whereas 72% to 89% are positive for the TTF-1 clone SPT24 and 77% to 90% for napsin A. 14,15,[25][26][27][28][29][30][31][32][33][34][35] Mucinous and solid predominant ACs are more frequently negative, 26,28,[36][37][38] and they constituted 28% and 40% of the IHC-negative AC cases in our material, respectively. Likewise, studies have shown that 79% to 94% of lung SCC cases are positive for CK5 (or CK5/6), 76% to 100% for p40, and 87% to 100% for p63.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a further understanding of the tumorigenesis and biology of lung cancer might be useful for the development of novel prognostic markers or therapeutic targets in lung adenocarcinoma. We previously generated monoclonal antibodies to tumor‐associated proteins using lung cancer cells or tissues, termed the random immunization method . The present study describes one antibody, designated KU‐Lu‐10, which recognizes the inner membrane mitochondrial protein (IMMT) by immunoprecipitation and mass spectrometry (Supplementary Data S1 and Fig S1).…”
Section: Introductionmentioning
confidence: 99%
“…We previously generated monoclonal antibodies to tumor-associated proteins using lung cancer cells or tissues, termed the random immunization method. [2][3][4] The present study describes one antibody, designated KU-Lu-10, which recognizes the inner membrane mitochondrial protein (IMMT) by immunoprecipitation and mass spectrometry (Supplementary Data S1 and Fig S1).…”
Section: Introductionmentioning
confidence: 99%